2020
DOI: 10.7150/thno.45825
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed non-invasive tumor imaging of glucose metabolism and receptor-ligand engagement using dark quencher FRET acceptor

Abstract: Rationale: Following an ever-increased focus on personalized medicine, there is a continuing need to develop preclinical molecular imaging modalities to guide the development and optimization of targeted therapies. Near-Infrared (NIR) Macroscopic Fluorescence Lifetime Förster Resonance Energy Transfer (MFLI-FRET) imaging offers a unique method to robustly quantify receptor-ligand engagement in live intact animals, which is critical to assess the delivery efficacy of therapeutics. However, to date, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 70 publications
6
35
0
Order By: Relevance
“…The fluorescent lifetime decay graph ( Figure 3 B) and frequency graph ( Figure 3 C) demonstrate a significant reduction of donor lifetime in the presence of acceptor (A:D = 2:1), indicating FRET events due to HER2–TZM binding. As expected for FRET measurements of receptor–ligand interactions, e.g., TfR–Tf complexes [ 17 , 19 , 24 ], both HER2–TZM FRET donor fraction (FD%) and FRET efficiency ( E ) display rising trendlines when plotted against increasing A:D ratios ( Figure 3 D,E). Interestingly, the average FD% values are similar for both TfR–Tf and HER2–TZM complexes in cancer cells ( Supplementary Figure S3 ) [ 17 , 19 , 24 ].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The fluorescent lifetime decay graph ( Figure 3 B) and frequency graph ( Figure 3 C) demonstrate a significant reduction of donor lifetime in the presence of acceptor (A:D = 2:1), indicating FRET events due to HER2–TZM binding. As expected for FRET measurements of receptor–ligand interactions, e.g., TfR–Tf complexes [ 17 , 19 , 24 ], both HER2–TZM FRET donor fraction (FD%) and FRET efficiency ( E ) display rising trendlines when plotted against increasing A:D ratios ( Figure 3 D,E). Interestingly, the average FD% values are similar for both TfR–Tf and HER2–TZM complexes in cancer cells ( Supplementary Figure S3 ) [ 17 , 19 , 24 ].…”
Section: Resultssupporting
confidence: 67%
“…As expected for FRET measurements of receptor–ligand interactions, e.g., TfR–Tf complexes [ 17 , 19 , 24 ], both HER2–TZM FRET donor fraction (FD%) and FRET efficiency ( E ) display rising trendlines when plotted against increasing A:D ratios ( Figure 3 D,E). Interestingly, the average FD% values are similar for both TfR–Tf and HER2–TZM complexes in cancer cells ( Supplementary Figure S3 ) [ 17 , 19 , 24 ]. To exclude molecular crowding effects, we have previously demonstrated that FLIM-FRET behaves independently from increasing acceptor concentration [ 16 , 31 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…For example, FMT has been used in conjunction with structured light illumination to achieve quantitative 3D FRET tomographic non-invasive in vivo macroscopic FLI (MFLI) imaging of subcutaneous tumor xenografts to measure drug delivery (Rudkouskaya et al, 2018(Rudkouskaya et al, , 2020b. Subsequently, in vivo multiplexed MFLI-FRET imaging of receptor-ligand target engagement and glucose metabolism in tumor xenografts in live intact animals has been demonstrated (Rudkouskaya et al, 2020a). However, tomographic image reconstructions are computationally expensive and require expertise in light propagation modeling, limiting their use in biomedical applications (Leblond et al, 2010).…”
Section: Contrast Enhancement For High-performance 3d Imaging and Super-resolution Microscopymentioning
confidence: 99%
“…Fluorescence imaging has become a central tool in biomedical studies with high sensitivity to observe endogenous molecules [70,71] and monitor important biomarkers [72]. Increasingly, fluorescence imaging is not limited to intensity‐based techniques but can extract additional information by measuring fluorophore lifetimes [73–75].…”
Section: Applications In Biomedical Opticsmentioning
confidence: 99%